COVID-19 pandemic in an Italian obstetric department: sharing our experience - Driul, Lorenza; Meroi, Francesco; Cecchini, Fabiana; Sala, Alessia; Orso, Daniele; Padovani, Diana; Rovida, Serena; Dogareschi, Teresa; Vetrugno, Luigi; Bove, Tiziana (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work: The outbreak of the novel coronavirus (or SARS-CoV 2) has significantly struck the healthcare system worldwide. Over the course of a few weeks, hospitals reorganized their internal structure entirely at any level of care, from the Emergency rooms to Departments, including all the medical specialties. Methods: In order to cope with the contingent state of emergency, the Gynecology and Obstetrics Unit of the University Hospital in Udine introduced new protocols and guidance for the usual standard of care, ensuring a safe environment for both healthcare providers and patients. Results: By a continuous update of scientific evidence, the department was able to increase capacity as well as maintain flexibility when a higher number of admissions was required. Conclusion: We aimed to share our experience, which provided a relevant lesson about what to expect and how to prepare a referral center for high-risk pregnancy in response to a pandemic such as COVID-19.